Christianity from the Margins in Southeast Asia - Francisco, Jose Mario C. (Archīum Ateneo, 2024)
Studies on Christianity in Asia have been weighed down by a double burden—the commonplace of Christianity as a passive minority and an invading foreign as well as the notions of religion and secularization derived from western experience. The following essays of Forum Kritika shed both burdens by focusing on the “lived religion” of different Christian groups and leaders on the margins of Southeast Asian societies because of religious faith as well as ethnicity, status or location. Their critical analysis shows how these actors interacted with other social and cultural traditions and problematized narratives of identity linked to the dominant sociocultural ethos. These negotiations, far from being private and divorced from the institutional, point to the complex and dynamic nature of Christianity in the Asian landscape and to how Christian groups and individuals manage to hold their ground.